Effects of integrative administration of acetyl-L-carnitine, arginine, and Co-Q10 in mitigating oxidative stress in over-weight/obese PCOS women - Fawad Ali Shah, Syed Murtaza Shah Bukhari, Emal Emal, Mohsin Shah (Journal of Applied Pharmaceutical Science, 2025)
Polycystic ovary syndrome (PCOS) is a common multifactorial endocrine reproductive disorder affecting 11%– 13% of women worldwide. This study evaluated the effects of integrative therapy on oxidative stress as well as hormonal and metabolic parameters in women affected by PCOS. Sixty women with PCOS were randomly assigned to either an integrative therapy group, receiving acetyl-L-carnitine (ALC) (2,000 mg), L-arginine (2,000 mg), and Coenzyme Q10 (Co-Q10) (200 mg) daily, or a metformin group, receiving metformin (1,000 mg daily) for a 12-week period. Baseline values were comparable between both groups. Before treatment, both arms exhibited significantly elevated oxidative stress, alongside alterations in anthropometric, metabolic, and endocrine parameters. The treatment significantly altered the anthropometric profiles of participants in both treatment arms (p < 0.05). The integrative therapy led to a greater reduction in oxidative stress markers, such as carbonyl and asymmetric dimethylarginine levels (p < 0.05) compared to the metformin group. The integrative therapy group also showed significant improvements in hormonal parameters, Ferriman–Gallwey scores, and ovarian morphology compared to the improvements observed in the metformin group (p < 0.05). This randomized control trial demonstrated that integrative therapy with ALC+Arg+Co-Q10 significantly improved oxidative stress, and metabolic, and endocrine profiles in overweight/obese women with PCOS. The findings highlight the potential of this integrative therapy as a comprehensive treatment strategy for PCOS. Trial Registration: ClinicalTrials.gov NCT05653895. Registered: 3 January, 2022.
Keywords: Acetyl-L-carnitine, polycystic ovary syndrome, arginine, Co-Q10 therapy